Predictive factors of health promoting behavior in nursing teachers from three universities in Cali, Colombia - Triviño-Vargas, Zaider Gloria; López-Hurtado, María Ximena (Universidad y Salud, 2018)
Introduction: Health promotion has been a constant concern in the human being. It allows to understand behaviors related to it and orientates towards the generation of health promoting behaviors (HPB) that promote personal well-being. Objective: To determine the predictor factors influencing the HPB of the teachers according to Pender’s health promotion model. Materials and methods: A correlational descriptive design was made with a representative sample of the teachers with current contract during the study. Instruments such as the EVPS II scale of Pender were applied to measure the dependent variable CPS, as well as for the independent ones such as sociodemographic, knowledge on health promotion, perception of health status and perception of self-efficacy. Results: They are descriptive, according to the coefficient of variation in each of the subdimensions of the behaviors: spiritual growth, interpersonal relations, responsibility in health, nutrition, management of stress and physical activity. The predictor factors were based on the multiple regression model. Conclusions: Favorable HPB were spiritual growth, interpersonal relationships and nutrition. Predictors that have effect on HPB were presented on the basis of teacher rankings, age, senior adult performance area, stratum, income and area of performance, mental health and psychiatry.